Analysis of A.C. and D.C. Circuits - Basic Calculations - Prudhomme, William (McGraw-Hill's AccessEngineering., 2015)
Software simulation programs are generally used for modeling and designing complex electronic circuits and applications, but frequently only a basic calculation is needed to solve an immediate design problem or to calculate the value of a specific circuit element. This Excel workbook addresses this need by automating the calculation of over 70 basic electronics formulas in direct current (d.c.) and alternating current (a.c.) circuits and applications. The workbook includes worksheets on: 1. Basic Formulas (d.c.): Ohm's Law for d.c. circuits (voltage, current, resistance, and power). 2. Basic Formulas (a.c.): Ohm's Law for a.c. circuits (voltage, current, impedance, power, and power factor). 3. Basic Series Circuits: Calculation of impedance, phase angle, and reactance for series RL, RC, LC, and RLC circuits and total resistance for pure series resistive circuits. 4. Basic Parallel Circuits: Calculation of impedance, phase angle, and reactance for parallel RL, RC, LC, and RLC, series/parallel RL/RC, series/parallel RL/C, series/parallel L/RC and total resistance for pure parallel resistive circuits. 5. Networks: Kirchhoff's Laws, Superposition, Thevenin, Norton and Millman Theorems (presents theorems and methods to solve). 6. Alternating Current/Voltage: Calculation of rms, peak, peak-to-peak, average voltage/current, in addition to frequency, period, wavelength, power, apparent power, reactive power, and power factor.